One-dimensional multi-period cutting stock problems in the concrete industry - Signorini, Caroline de Arruda [UNESP]; de Araujo, Silvio Alexandre [UNESP]; Melega, Gislaine Mara (Taylor & Francis, 2021)
This research looks at the production planning of hollow-core slabs integrated to the optimisation problem of the use of moulds. Considering the production process of these structures, two mathematical models are proposed for the arising problem, which consists of a one-dimensional multi-period cutting stock problem with innovative aspects regarding the multiple manufacturing modes that can be used to produce the slabs. In addition, a theoretical analysis of the proposed models is presented. These models are solved using heuristic methods, both aiming to minimise production and inventory costs. Using data based on real information provided by a company, the computational results showed that the heuristic based on the compact model performed better than the one based on the extended model, due to some characteristics specific to the problem being studied.
Keywords: column generation; hollow-core slabs production; Mathematical modelling; multi-period cutting stock problem; relax-and-fix